The ant genus Linepithema (Formicidae: Dolichoderinae) in Colombia - Escárraga, Mayron; Guerrero, Roberto J. (Zootaxa, 2016)
The species of Linepithema Mayr in Colombia are reviewed from collection material. The genus Linepithema comprises 20 species, of which the following are reported in Colombia: L. angulatum (Emery), L. dispertitum (Forel), L. gallardoi (Brèthes), L. humile (Mayr), L. iniquum (Mayr), L. neotropicum Wild, L. piliferum (Mayr), L. tsachila Wild, and a new species, Linepithema hirsutum sp. nov. Linepithema dispertitum is a new record for Colombia and South America. A taxonomic key (English and Spanish) and distribution maps to the species of Linepithema in Colombia are provided.